Identification of Digital Marketing Improvement Strategies for MSME Products and Services Post-Covid-19 Pandemic in Indonesia - Purbaningsih, Yuli; Sulistiyo Nugroho, Budi; Nurfauzi, Yogi; Hendrik Sitaniapessy, Rainier; Towpek, Hadenan (Jurnal Manajemen Industri dan Logistik, 2022)
The strategy to improve digital marketing for MSME products and services is a critical study. Therefore, the authors are interested in reviewing scientific evidence of increasing digital era MSME marketing to increase understanding. Finally, we can conclude that the findings include several strategies to increase the promotion of MSME products and including MSME managers preparing products and services that have future value and serving customers better, making the best buyer journeys, understand when and how to fix any shortcomings, develop periodic promotions, optimize website promotions, develop internet promotions, always place website pages easy to find, review items, create a business Google account, participate, participate, influencers, then right-click, are virtual entertainment. It is hoped that this study will become a vital force in increasing the understanding of digital marketing strategies in MSME businesses.